(untitled) (PJDOL, 2023)
The quest for university education has led to the increased demand for Open Distance Learning Options in Nigeria, moreso when the Conventional Universities have very limited enrolment spaces. However, many of the ODL students were faced with Challenges in pursuit of the programme which results in lower completion rates. This research work examined the influence of these challenges on the ODL students completion rate.Descriptive survey reseach design was used for the study. It covers all Business Education students in the ODL programme of the National Open Unviersity of Nigeria (Ilorin Study Centre) and the Unviersity of Ilorin.